An Empirical Assessment of the Contribution of State Offices of Inspectors General to Corruption Control. (2nd January 2022) - Kempf, Robin J.; Sampath, Vijay S.; Lu, Elaine Yi; Shapiro, David M.
Abstract : This exploratory research examines whether the proliferation of state offices of inspector general (OIGs) contributes to corruption control. Using 50-state panel data from 1976 to 2010, preliminary evidence that the number of state-level OIGs is positively associated with the corruption conviction rate is shown. This suggests that state OIGs act as a successful corruption detection mechanism, and therefore, OIGs play a role in corruption control, working to help keep the government accountable.